2020
DOI: 10.4102/sajhrm.v18i0.1326
|View full text |Cite
|
Sign up to set email alerts
|

Leadership contingencies in the retention of women in higher education

Abstract: Orientation: Providing leadership opportunities and eliminating barriers to advance to or remain in leadership positions may influence the retention of women at academic institutions.Research purpose: The purpose of this study was to determine the impact of leadership contingencies on the retention of women.Motivation for the study: Women could be better equipped to succeed in leadership roles if more is known about the challenges they face to advance to or remain in leadership positions and how these challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…According to the most recent employment equity statistics, women hold between 23.5% and 34.5% of top management and senior management positions (Department of Labour, 2019). Consequently, past gender imbalances are slowly eradicated, and women's advancement to senior management positions is neglected (Coetzee & Moosa, 2020;Osituyo, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the most recent employment equity statistics, women hold between 23.5% and 34.5% of top management and senior management positions (Department of Labour, 2019). Consequently, past gender imbalances are slowly eradicated, and women's advancement to senior management positions is neglected (Coetzee & Moosa, 2020;Osituyo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our research closes an important gap by providing empirical evidence on women's unique experiences in senior leadership positions. Women leaders can be better equipped and prepared for future leadership roles if more information about the challenges they face is available (Coetzee & Moosa, 2020). According to Nkomo and Ngambi (2009, p. 50), 'scholars cannot ignore or misunderstand the status, experiences, and roles of women leaders in the African business context, as well as the challenges to their success'.…”
Section: Introductionmentioning
confidence: 99%
“…This also reflected in Figure 1 with yearly percent of female employees who exited the institution's employment seemed higher than that of males when combined over the 5-year period. Bartels et al (2021), acknowledged similar trend in their study describing the attrition of female employees in academia as a leaky pipeline, which has called for greater concern in the field of human resource management, according to Coetzee & Moosa (2020). Kanyumba and Lourens (2021) attributed the increasing attrition rate to the inability of HE institutions to recruit, retain and promote females in academia.…”
Section: Discussionmentioning
confidence: 94%
“…46 Similarly, studies of academia from a range of countries have found high attrition among female faculty, with cascading consequences as female students have reduced access to mentorship from women in their fields. 47 Women's longer average time to tenure-driven by women's high contributions to teaching and mentoring when this work is devalued compared to publications in tenure decisions; the penalization of women when they coauthor and collaborate in circumstances where men are not penalized; and the lack of flexibility for temporary part-time work to count toward tenure, which disproportionately affects women who have children-is one explanation for these departures. 48 Gender also shapes vulnerability to job loss when a company is downsizing.…”
Section: Discrimination and Disparities In Terminationsmentioning
confidence: 99%